Short-beam shear fatigue behavior of fiber metal laminate (Glare) - Kotik, Hector Guillermo (2017)
Interlaminar shear stresses have an important role in behavior of fiber metal laminates (FMLs). Low interlaminar shear strength in the crack bridging mechanism of these materials is considered beneficial because produces delamination and this prevents fiber failure; although when this strength is too low excessive delamination can occur, leading to a less efficient mechanism. This strength also has important roles in fatigue crack nucleation of internal laminae and in cases where the material is subject to shear stresses. This paper studied quasi-static and fatigue (R = 0.1; 5 Hz) interlaminar shear behavior of a commercial FML (Glare 1 3/2) employing the short-beam shear (SBS) test in longitudinal and transversal orientations. Failure modes and the limitations of the SBS test to characterize the interlaminar shear fatigue behavior are described and discussed.